The river swimmer [large type] : novellas - Harrison, Jim, 1937-2016 (Thorndike Press, A part of Gale, Cengage Learning, 2013)
His latest collection of novellas is Jim Harrison at his most memorable. In The Land of Unlikeness, a sixty-year-old divorced art history academic reluctantly returns to his family's Michigan farmhouse to visit his aging mother. Water Baby ventures into the magical as an Upper Peninsula farm boy, drawn to the water as an escape, sees otherworldly creatures there. The River Swimmer is a striking portrait of two richly-drawn, profoundly human characters. (Bestseller)